The edge of the world : a cultural history of the North Sea and the transformation of Europe - Pye, Michael, 1946- (Pegasus Books, 2015)
Tells the story of how modernity emerged on the shores of the North Sea, uncovering a lost history of a thousand years rife with saints, spies, pirates, philosophers, artists, and intellectuals.